Shifts in Portfolio Preferences of International Investors: An Application to Sovereign Wealth Funds. Issue 5 (22nd October 2013) - Sá, Filipa; Viani, Francesca
Abstract: We develop a dynamic general equilibrium model to analyze the macroeconomic effects of a shift in portfolio preferences of foreign investors. The model has two countries and two asset classes (equities and bonds). It is characterized by imperfect substitutability between assets and allows for endogenous adjustment in interest rates and asset prices. To illustrate the mechanics of the model, we calibrate it to analyze a transfer of reserves from central banks to sovereign wealth funds (SWFs). We look separately at two diversification paths: a shift away from dollar assets (path 1), and a shift away from US bonds to US equities (path 2). In path 1, the dollar depreciates and US net debt falls on impact and increases in the long run. In path 2, the dollar depreciates and US net debt increases in the long run.